The pricing of manufactures - Barback, R. H. (London : Macmillan, 1964)
This book points to prices of manufactures by way of full cost the economists use for cost implication in manufacturing industry.
Includes bibliographical references and index.
mf 24/01/2019
Loans
Keywords: Prices